2020
DOI: 10.3389/fpsyt.2020.00331
|View full text |Cite
|
Sign up to set email alerts
|

Metaphor Processing Dysfunctions in Schizophrenia Patients With and Without Substance Use Disorders

Abstract: Background: Patients with schizophrenia have difficulties comprehending metaphors, which significantly impedes communication. However, this topic has not been thoroughly studied in people with a dual diagnosis. On this basis, we formulated two research aims: a) to compare the ability to comprehend metaphors in schizophrenia patients without (SZ) and with substance use disorder (SZ-SUD) and b) to determine the relationship between the processing of metaphorical content and the severity of psychopathological sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
1
1
0
1
Order By: Relevance
“…This, supports the definition of the DSM 5, which states that cognitive dysfunction is a common aspect of this diagnosis, as it is present at the onset of the disease, as well as in the course, which lingers with cognitive deficits established even in adult age, and can persist even when the positive and negative symptoms disappear, contributing noticeably to the disability that causes difficulties in academic and labor processes (APA, 2013) Thus, it can be identified that alterations in cognitive functioning manifest globally, resulting in cognitive impairment rather than deficits in a single area of mental processing. These findings are consistent with the results found by different studies, which determine the importance of the involvement of cognition in this type of disorder since cognitive dysfunction is part of the common alterations of the disease (Penadés et al 2015), which is consistent with the results of Lozano and Acosta (2009), who complement that these alterations are present in the global cognition of patients affecting multiple domains, such as attention, memory, executive functions, motor skills and social and affective cognition, which can be synthesized in three fundamental structures "(1) cognitive flexibility, (2) interference and memory control and (3) processing speed and attention" (Gaviria et al 2017, p. 124;Peña et al, 2018;Sahbaz & Kurtulmus, 2019;Karabanowicz et al, 2020;Alkan et al, 2021;Ochoa-Jimenez., Sánchez y Herrera, 2023) It was observed that subjects with a better attitude of acceptance and a positive attitude towards medication performed worse on neuropsychological tests in the domains of verbal fluency, semantic and motor functions. Stroop-time interference is part of executive functions.…”
Section: Discussionsupporting
confidence: 89%
“…This, supports the definition of the DSM 5, which states that cognitive dysfunction is a common aspect of this diagnosis, as it is present at the onset of the disease, as well as in the course, which lingers with cognitive deficits established even in adult age, and can persist even when the positive and negative symptoms disappear, contributing noticeably to the disability that causes difficulties in academic and labor processes (APA, 2013) Thus, it can be identified that alterations in cognitive functioning manifest globally, resulting in cognitive impairment rather than deficits in a single area of mental processing. These findings are consistent with the results found by different studies, which determine the importance of the involvement of cognition in this type of disorder since cognitive dysfunction is part of the common alterations of the disease (Penadés et al 2015), which is consistent with the results of Lozano and Acosta (2009), who complement that these alterations are present in the global cognition of patients affecting multiple domains, such as attention, memory, executive functions, motor skills and social and affective cognition, which can be synthesized in three fundamental structures "(1) cognitive flexibility, (2) interference and memory control and (3) processing speed and attention" (Gaviria et al 2017, p. 124;Peña et al, 2018;Sahbaz & Kurtulmus, 2019;Karabanowicz et al, 2020;Alkan et al, 2021;Ochoa-Jimenez., Sánchez y Herrera, 2023) It was observed that subjects with a better attitude of acceptance and a positive attitude towards medication performed worse on neuropsychological tests in the domains of verbal fluency, semantic and motor functions. Stroop-time interference is part of executive functions.…”
Section: Discussionsupporting
confidence: 89%
“…This might be due to the difficulty of transforming verbal information into visuals. After verbal instructions, the visual mental images might become somewhat intrusive in the visual task [ 60 ]. Additionally, lexical and semantic disorders may be associated with lower inference ability and cause problems understanding more linguistically complex texts [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cognición en la esquizofrenia. Revisión sistemática deterioro cognitivo mayor (Chattopadhyay et al, 2020;Gopal et al, 2020;Karabanowicz et al, 2020;Sahbaz y Kurtulmus, 2019;Valaparla et al, 2017).…”
Section: Cognición Asociada a La Fase De La Enfermedadunclassified